Activity of lipopolysaccharide-binding protein-bactericidal/permeability-increasing protein fusion peptide in an experimental model of Pseudomonas sepsis. - Opal, S M (1995)
A chimeric protein consisting of the N-terminal domain of lipopolysaccharide-binding protein and the C-terminal domain of bactericidal/permeability-increasing protein demonstrated a dose-dependent survival benefit (P = 0.001) and reduced endotoxin levels (P < 0.01) in neutropenic rats with Pseudomonas aeruginosa sepsis. This lipopolysaccharide-binding protein-bactericidal/ permeability-increasing peptide has favorable pharmacokinetics and antiendotoxin properties which may be of value for human sepsis.